P413 A dyadic intervention for STI prevention in youth: feasibility, acceptability & preliminary effectiveness. (14th July 2019) - Matson, Pamela; Rowell, Julia; Toppins, Jacquelin; Woods, Colin; Huettner, Steven; Robinson, Camille; Fields, Errol; Marcell, Arik; Trent, Maria
Abstract : Background: Sexually transmitted infection (STI) prevention strategies for adolescents and young adults (AYA) primarily rely on individual approaches leaving sexual partners with significant unmet sexual and reproductive health needs. This paper describes the research methods and preliminary feasibility, acceptability, and preliminary effectiveness of a dyad-based behavioral intervention that augments individual evidence-based interventions with joint health education counseling for STI-affected AYA dyads within a primary care setting. Methods: Index participants were AYA 15–25 years, engaged in heterosexual intercourse, history of positive STI, Baltimore City resident, willing to recruit their main sexual partner for the study. Exclusions include: one or both partners has HIV infection, pending incarceration, greater than five years age difference, evidence of partner violence. Index and partner completed a single individual session separately with a gender-matched health educator. Dyads were randomized to receive an additional joint debriefing session together, and separately completed a telephone interview 6 weeks post intervention. Results: 18 dyads were recruited over 11 months. Mean age [range] females: 21.5 [17–26], males: 22.7 [18–27]. Mean age difference within dyads: 1.4 years. Acceptability was high with 100% agree/strongly agree it was a great opportunity to reflect on relationship with their partner and a worthwhile use of their time. More in the intervention group endorsed feeling closer to their partner than when they arrived for the visit (94 vs 88%). 100% of dyads were still together at 6 weeks. Participants reported high confidence that they could negotiate condom use with their partner even if partner did not want to, mean 9.3 (sd =2.2) out of 10. Conclusion: AYA endorsed helpfulness of the intervention. Participants showed high confidence in condom negotiation with their partner 6 weeks following the intervention. Recruitment of AYA dyads is a challenge, and more successful with young adults; however, dyadic interventions show promising impact on behavior that can prevent STI. Disclosure: No significant relationships.